Phenomenon of Psychological Well-Being in the Context of Medical Students' Satisfaction with Educational Activities - Yulia Y. Kochetova; Oksana G. Barinova; Nataliya S. Timchenko (National Research Mordova State University, 2024)
Introduction. Preservation and strengthening of mental and psychological health of students is one of the priority tasks of development of modern professional education in Russia. However, the recent studies into psychological well-being of medical students have shown an average and low level of its formation. The discovered problem is complicated by the lack of studies that would show the relationship between the peculiarities of the organization of the university educational environment and the satisfaction with the learning activities of students. This is important for the development and practical realization of optimal conditions for the formation of psychological well-being of medical university students. The aim of the study is to determine the specifics of the state of psychological well-being of medical university students in connection with the level of their satisfaction with learning. Materials and Methods. First, second and fifth-year medical students participated in the servey. The following diagnostic tools were used: "Scale of psychological well-being" (K. Riff) and "Questionnaire of satisfaction with educational activities" (L. V. Mishchenko). The analysis of the results of the study revealed statistically significant correlations between the scales of satisfaction with the educational activities of medical university students and their psychological well-being. Results. The analysis of the results of the study revealed statistically significant correlations between the scales of satisfaction with learning activities of medical students and their psychological well-being. Second-year students demonstrated high indicators of psychological well-being, the lowest ones were found in fifth-year students. The obtained results create prerequisites for comprehension of the process of optimizing the educational environment of medical school, focused on the preservation and promotion of mental health of students. Discussion and Conclusion. The conclusions of this study can be useful for the management corps of the university in order to develop and implement optimal psychological and pedagogical conditions for the organization of the educational environment and increase the level of satisfaction in the student community with all components of the structure of learning activities as one of the main conditions for the development of psychological well-being of young people.